Recovery of Pure Silicon and Other Materials from Disposed Solar Cells. (16th April 2021) - Punathil, Lineesh; Mohanasundaram, K.; Tamilselavan, K. S.; Sathyamurthy, Ravishankar; Chamkha, Ali J.
Abstract : The disposal of used photovoltaic panels is increasing day by day around the world. Therefore, an efficient method for recycling disposed photovoltaic panel is required to decrease environmental pollution. This work is aimed at efficiently recovering pure silicon and other materials such as aluminium, silver, and lead from disposed solar cells using chemical treatments. Earlier, the pure silicon was recovered by treating the solar cells with hydrofluoric acid or mixture of hydrofluoric acid and other chemicals. The usage of hydrofluoric acid is eliminated in the present work as it is highly toxic and corrosive chemical. The pure silicon (99.9984%) has been recovered by sequentially treating with three different chemicals. Aluminium, silver, and lead are also recovered as aluminium hydroxide, silver chloride, and lead oxide, respectively.